Analisis Resepsi Penonton Mengenai Hubungan Beda Agama dalam Film Akhirat: A Love Story - Adzriansyah, Mochammad Fegi; Delliana, Santi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
Films do not become a reflection of reality in a real building. This research is in progress to find out the reception of the film Akhirat: A Love Story in Jakarta, the plot of the film Akhirat: A Love Story which addresses the issue of interfaith marriages. The theory used in this research is the theory of encoding and decoding. This research uses qualitative accession with reception analysis method. The results of this research show that the four informants in this research agree that Akhirat: A Love Story is a film that has a narration as strong as that of a different religion. On the other hand, the three informants in posizi oposizi aka this film also reflect on the causes and effects of religious entities that are embedded in an image of romance. According to the informant, Sanghe is in a position of negotiation, takama, describing the blessing of parents, as well as the struggle of appearances of different religions is described in a sequence of psychological and physical conditions. Informants in the dominant position of ipsuttu akaa who do not approve of romantic relationships of different religions are wise liars.